How Should Oxygen Supplementation Be Guided by Pulse Oximetry in Children: Do We Know the Level? - Langley, Ross; Cunningham, Steve (Frontiers in Pediatrics, 2017)
Supplemental oxygen is the one of the most commonly prescribed therapies to children in hospital, but one of the least studied therapeutics. This review considers oxygen from a range of perspectives; discovery and early use; estimate of oxygenation in the human body – both clinically and by medical device; the effects of illness on oxygen utilisation; the cellular consequences of low oxygen; and finally how clinical studies currently inform our approach to targeting supplementing oxygen in those with lower than normal oxygen saturation.